Frufous System: A Simple Water Purifier with Hydro Filter Tool - I Kusumawati; Juhari Juhari; Suryati Suryati (International Journal of Multi Discipline Science, 2021)
Water pollution is a change condition in a water reservoir such as lakes, rivers, oceans, and groundwater due to human activities. This pollution causes many aquatic organisms to die and causes various diseases. Based on these problems, a solution is needed to deal with water pollution. The solution was given in the manufacture of a simple water purifier that can be used at home, namely the Frufous water purifier system. The method used in this research was research and development (R & D) with a level of difficulty at level 1, namely researching without testing the product. The product was researched and developed as an alternative water filter by applying the Frufous system (From Us For Us). Validation of this product was carried out internally in a Focus Group Discussion (FGD). The product had been repaired according to the judgment and suggestions of expert and practitioner opinions. The product design had been declared internally tested. The results of this research and product development showed products that are original, functional, complex, and authentic. The Frufous water purifier system was complex so that it could filter dirty water into clean and clear water, compared to being untreated/filtered. This research was expected to be used as an inspiration for research ideas to be applied at an advanced level of difficulty, which can be tested externally and applied en masse.